1995
DOI: 10.1002/anie.199509701
|View full text |Cite
|
Sign up to set email alerts
|

The Catalytic Oxidative Coupling of Methane

Abstract: One of the great challenges in the field of heterogeneous catalysis is the conversion of methane to more useful chemicals and fuels. A chemical of particular importance is ethene, which can be obtained by the oxidative coupling of methane. In this reaction CH4 is first oxidatively converted into C2H6, and then into C2H4. The fundamental aspects of the problem involve both a heterogeneous component, which includes the activation of CH4 on a metal oxide surface, and a homogeneous gas‐phase component, which inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
457
0
11

Year Published

1998
1998
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 675 publications
(480 citation statements)
references
References 89 publications
12
457
0
11
Order By: Relevance
“…The catalytic conversion of methane to desired commodity chemicals is a challenging approach for the utilization of natural gas resources (1,2). Several recent studies have demonstrated that methane can be converted to benzene in the absence of an oxidant, such as oxygen, and the main literature results are summarized in Table 1 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The catalytic conversion of methane to desired commodity chemicals is a challenging approach for the utilization of natural gas resources (1,2). Several recent studies have demonstrated that methane can be converted to benzene in the absence of an oxidant, such as oxygen, and the main literature results are summarized in Table 1 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…However, some active TMI's, in particular Mo, show little or no activity in other characterization studies (3,4). Thus, it seems 1 On leave from the Centrum voor Oppervlaktechemie en Katalyse, Departement Interfasechemie, K. U. Leuven, Kardinaal Mercierlaan 92, 3001 Heverlee, Belgium. 2 To whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…It is enclosed by an electrical furnace (not shown in the drawing), the temperature of which is monitored using a thermocouple. The gas flow is regulated by calibrated mass-flow controllers for CH 4 , O 2 , and Ar/He mixture (8 vol-% He in Ar, serving as internal standard and carrier gas for the analytics).…”
Section: Profile Reactor Measurementsmentioning
confidence: 99%
“…Another reason for using Ar as 50th species was that all numerical rounding errors as well as errors from the mixture averaged diffusion treatment were lumped in the Ar mass fraction. The process was repeated for CH 4 /O 2 feed ratios ranging from 4, 8 and 16, temperatures at 700 and 1100 K, and pressures of 1 and 8 bar. An alternative approach is to use the absolute flux through each reaction, rather than its sensitivity coefficient.…”
Section: Mechanism Reductionmentioning
confidence: 99%
See 1 more Smart Citation